Tropology, Agency, and Historical Languages in Hayden White - Nicolás Lavagnino (Ideas y Valores, 2011)
This article addresses three issues closely related to current developments in philosophy and epistemology of history. First, it addresses the narrative deployment of historiographic discourse according to the original framework of Hayden White’s narrativist philosophy of history, centered on tropology as a basic method of historical cognition. Secondly, it examines how the application of tropology to historiography has raised questions about the status of historical knowledge, resulting in concerns about relativism, “linguistic solipsism”, truth, and justification. Finally, the paper addresses the fact that narrativism has been seen as opting for a merely literary or fictional view of the past. On that basis, it goes on to propose a narrativist perspective that avoids skeptical and relativistic interpretations, while at the same time reconsidering the concept of literature as a better way of understanding the tropological nature of the language used to give an account of the past.